(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Dharmayanti N, Anti A, Siregar RR, Sipahutar Y, Permadi A, Siregar AN, Salampessy RB, Sujuliyanti, Nurbani SZ, Purnamasari HB. 2021. Title. Biodiversitas 22: 373-378. Brown seaweeds have the potential to produce bioactive compounds. Bacteria associated with seaweeds are involved in the production of metabolites. Microbes may be present as a living symbiotic in association with other algae as epiphytes or endophytes. In this study, bacteria isolated from brown seaweed (Turbinaria conoides) were tested for antibacterial activity. A total of 14 bacteria were isolated, of which 6 were isolated from external tissue, while 8 from internal tissue. Results of an antagonistic test revealed that 7 isolates showed inhibitory activity against Staphylococcus aureus and only 1 isolate showed the inhibition against both S. aureus and Escherichia coli. Phenotypic and genotypic analysis showed that the symbiont bacteria was Lactobacillus plantarum.